Genome-wide association study revealed genetic loci for resistance to fusarium wilt in tomato germplasm - Kawicha, Praphat; Tongyoo, Pumipat; Wongpakdee, Somporn; Rattanapolsan, Ladawan; Duangjit, Janejira; Chunwongse, Julapark; Suwor, Patcharaporn; Sangdee, Aphidech; Thanyasiriwat, Thanwanit (My University, 2023)
Tomato Fusarium wilt caused by Fusarium oxysporum f.sp. lycopersici (Fol) constrains tomato production worldwide. Three hundred forty tomato accessions were evaluated for Fusarium wilt resistance and single nucleotide polymorphisms (SNPs) associated with resistance. The disease resistance evaluation revealed that 15, 13, and 15 accessions were identified as Fusarium wilt resistant in Test 1, 2, and Mean data, respectively, with the disease severity index (DSI) ranging from 0-16.7%. A genome-wide association study (GWAS) identified SNPs associated with resistance. Eighteen common SNPs were detected in at least two tests and located on chromosomes 4, 6, 7, 9, and 12. Six unique significant SNPs were found in either Test 1 or 2, located on chromosomes 2, 4, and 7. Candidate genes associated with Fusarium wilt resistance were identi-fied. Notably, two genes encoding leucine-rich repeat-like protein and disease-resistance protein were predicted from the two unique SNPs, solDsnp10606 and solDsnp6266, respectively.
Keywords: DArTseq; disease resistance; fusarium wilt; GWAS; tomato